(untitled) (Revista Argentina de Musicología, 2009)
This article analyzes the role of the rock producer in Argentina, conceiving him as a key mediator in the complex process that includes the recording of music with some kind of device. His work became increasingly important and is considered both coercive and creative at the same time. Our attention is focalized from the mid sixties to the mid seventies, as the first discographies initiatives arose in Buenos Aires independently from the multinational labels companies, and as the role of the artistic producer, differentiated from the executive producer, seems to have slowly and gradually emerged from anonymity.